Razão econômica, trabalho e produção de tecnologia: uma etnografia do mercado de eventos durante a COVID-19 no Brasil - Moreira, André Guilherme (Universidade Federal de São Carlos, 2022)
This dissertation seeks to understand the relation between economic reason, labor and technology production through the ethnography of Lúdica, an event production company that betwenn 2020 and 2021was faced with the COVID-19 pandemic in Brazil. With the ban of activities that generate gatherings by state and municipal authorities in March 2020 aiming to contain the increase of the coronavírus contagion rate in Brazil, Lúdica's revenues were reduced to R$ 0.00. Faced with this scenario, several tensions and contradictions emerged in the company involving discussions about work, technology, and the pandemic, which resulted in the reduction of the workforce while investing in technology. The ethnography, conducted remotely during the pandemic seeks to describe the knowledge, theories, practices, personal histories, and temporal representations that inform the world images, synchronic and diachronic, that guide the decision-making processes and actions of Lúdica's executives and employees. As I discuss throughout the dissertation, the “madness of economic reason” (DERRIDA, 1991) expressed in decisions such as that of the São Paulo State Government to relax isolation measures contrary to the orientation of epidemiologists, is the result not only of “company’s culture” or “public agencies”, but also the sociotechnical agencements, particular historical trajectories and temporal maps to which people are intertwined. These images about the world create paradoxes that propose us to reflect on how the economization of different aspects of life can lead to disastrous outcomes as happened in Brazil between 2020 and 2022. This dissertation, therefore, describes how entrepreneurs, employees, and some representatives of public power react in the face of a crisis, and how the images of the world that inform their decisions change according to the technologies and relationships to which they have access.
Economic reason, labor, and technology production: an ethnography of the events market during COVID-19 in Brazil
Keywords: Mercado; Economia; Estudos das organizações; Temporalidades; Pandemia; Market; Economy; Organization studies; Temporalities; Pandemic; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS